The Influence of Interactive Technologies on the Formation of Foreign of Foreign Language Communicative Competence of Students of Philology Majors - Andreya Pevse; Libak Natalka; Judit Pavlovich; Olena Stativka; Liudmyla Potenko; Андрея Певсе; Лібак Наталка; Юдіта Павлович; Олена Статівка; Людмила Потенко; Pősze Andrea; Libák Natálka; et al. (MAGNANIMITAS, 2022)
Abstract. The relevance of the topic is the need to improve modern pedagogical practice through the use of modern innovative tools, namely interactive technologies. The issue of using interactive technologies is the possibility of gaining competitive advantages in the cognitive activity of students. Students of philological specialties face the problems of lexicogrammar nature and heavy workload. From this point of view, the research topic is relevant and requires the development of a methodology for the implementation of foreign language communicative competence using interactive technologies. The issue of their use in the modern educational environment is due to the increased attention of scientists because the qualitative use of interactive technologies can qualitatively improve the activities of students of various cognitive natures. Through the use of interactive technologies, an educator who plans to conduct a seminar or lecture should be able to identify key tools aimed at developing the cognitive abilities of the student. This has led to the setting of goals and objectives for the study. The objectives of the study are to analyze modern means of interactive technologies that can qualitatively improve the conduct of seminars or lectures. Moreover, an important direction in the study is the analysis of modern existing methods that can qualitatively improve the policy of organizing training and change the education system following the development of digital and interactive technologies in the long term. The object of the study is the cognitive activity of students of philological specialties and interactive technologies as a tool to improve the quality of mastering the discipline. The introduction of interactive technologies will improve not only the quality of students’ foreign language communicative competencies but will also be able to provide an effective policy for communication among students. Through the use of scientific research methods and analysis of various types of interactive technologies, a thorough study of the development of interactive technologies and the quality of their formation in the modern educational environment can be carried out. The results obtained can improve modern teaching practices and increase the effectiveness of the implementation of foreign language communicative competence of students of philological specialties. The article investigates the basic principles of the development and formation of foreign language communicative competence through the introduction of interactive technologies in the educational process.
Keywords: foreign language; cognitive activity; interactive technologies; group projects; analytical skills; communicative competence; JEL Classification